PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA PT INDOCEMENT TUNGGAL PRAKARSA TBK PERIODE 2013-2022 - Sherin Putri Najwa Velisa; Siti Nurcahayati (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Current Ratio and Debt to Equity Ratio on Net Profit Margin at PT Indocement Tunggal Prakarsa, Tbk for the period 2013-2022. This research was conducted using the financial statements of PT Indocement Tunggal Prakarsa, Tbk 2013-2022. The data analysis method used is descriptive statistical test, classical assumption test, multiple linear regression analysis, t test hypothesis testing, f test, and R2 determination coefficient test. The t test results show that CR has a sig value of 0.007 <0.05 and a tcount value of 3.781> from t table 2.365, this indicates that partially CR has a significant effect on NPM. DER has a sig value of 0.321> 0.05 and a tcount value of 1.068 < from the t table 2.365, this indicates that partially DER is not significant to NPM. Then, the results through the f test have a significance value of 0.003 <0.05 and an Fcount value of 15.368> from Ftable 4.737, this indicates that simultaneously CR and DER have a significant effect on NPM. The result of the coefficient of determination (R2) test is 81.4%, this result shows that CR and DER have an influence of 81.4% and the remaining 18.6% is influenced by other variables not examined in this study.